Application of Tikhonov regularisation method in bounded chord subjected to enforcement. (1st January 2013) - Wang, Linjun; Xie, Youxiang
Inverse problem of identifying initial condition about forced vibration equation of chord is investigated. First, we separate the forward problem into two determinate problems by the superposition principle, and obtain the solution of direct problem by separate variable method and latent function method. Second, discrete it by trapezoidal formula method, and then obtain a severely ill-conditioned linear equation, which is sensitive to the disturbance of the right data. Thirdly, identify the initial condition by Tikhonov regularisation method. The numerical results confirm that this method is feasible and effective.